Aluminum lithium adsorbent and preparation method and application thereof
By controlling the Cl-concentration in the early stage of the reaction and introducing surfactants, the interface regulator and Al3+ chelation function, the aluminum-based lithium adsorbent oriented induces a layered structure during the crystal phase formation stage, solving the problems of heterogeneous heteronucleation and nano-scale agglomeration, improving the purity of the material and the diffusion rate of lithium ions, and achieving efficient lithium adsorption.
Patent Information
- Application Number
- CN202510778268.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-11
- Publication Date
- 2025-08-15
AI Technical Summary
The existing aluminum-based lithium adsorption materials have heterophasic nucleation and hard agglomeration of nano-scale precursors during the crystal phase formation stage, resulting in low lithium adsorption capacity, poor purity and blocked lithium ion diffusion path, affecting the stability of long-term operating performance.
By controlling the Cl-concentration at the beginning of the reaction, the surfactant and chloride salt are introduced, and the chelation of the interface regulator and Al3+ is used to induce the formation of a layered structure in a directionally, a through-mesoporous channel is constructed, and a high-active crystal surface is exposed, and the material purity and lithium ion diffusion rate are improved.
It has achieved high purity (≥95%), high adsorption capacity (10-15mg/g) and high lithium raw material utilization rate (≥90%) of aluminum-based lithium adsorbents, long-cycle stability, and is suitable for the recycling of lithium extraction and waste lithium batteries in salt lakes, reducing operating costs.
Smart Images

Figure CN120479371A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of functional material preparation, and in particular relates to an aluminum-based lithium adsorbent and a preparation method and application thereof. Background Art
[0002] In recent years, with the rapid development of the new energy vehicle industry, demand for lithium resources has seen exponential growth. Within the existing lithium resource development system, lithium extraction from salt lake brine has become a key strategic direction for global lithium resource development due to its large reserves and low mining costs. Among the currently industrially applied lithium extraction technologies, selective adsorption, due to its strong process compatibility and high environmental friendliness, has gradually become the mainstream technical path for lithium extraction from salt lakes.
[0003] In the adsorption technology system, aluminum-based lithium adsorption materials represented by layered double hydroxides (such as Li / Al-LDH) have shown excellent performance in Li adsorption due to their unique interlayer ion exchange mechanism. + Compared with manganese-based and titanium-based lithium adsorption materials, aluminum-based lithium adsorption materials have outstanding anti-dissolution properties and industrial production cost advantages, making them the only inorganic metal adsorbent currently available for large-scale application.
[0004] In the industrial preparation process of aluminum-based lithium adsorption materials, although the co-precipitation method has been applied on a large scale, its crystal nucleation-growth mechanism still has the following key defects: First, in the crystal phase formation stage, due to the Al in the reaction system 3+ 、Li + The mismatch between the local concentration gradient and the diffusion rate of the plasma leads to heterogeneous nucleation of Al(OH)3 heterogeneous phases. At the same time, the traditional process lacks effective particle dispersion control means, resulting in hard agglomeration of nanoscale precursors, which triggers a double negative effect: on the one hand, it reduces the utilization rate of the lithium source, resulting in low lithium adsorption capacity; on the other hand, it weakens the intercalation efficiency of the layered double hydroxide (LDH) for Cl-, resulting in poor product purity, which in turn affects the performance stability of the adsorbent during long-term operation. The above structural defects directly lead to a decrease in the density of lithium ion active sites inside the material and obstruction of the lithium ion diffusion path, which ultimately leads to a great difference between the actual lithium adsorption capacity of the powder material (4-8 mg / g) and the theoretical capacity (30-40 mg / g).
[0005] Therefore, how to solve the problems of limited adsorption capacity, insufficient phase purity and low utilization rate of raw lithium in aluminum-based lithium adsorption materials has become an innovative breakthrough direction for improving lithium extraction rate and process economy. Summary of the Invention
[0006] In view of the shortcomings of the prior art, the present invention aims to provide an aluminum-based lithium adsorbent and its preparation method and application. The present invention provides a "heterogeneous phase suppression-morphology control" dual-track synergistic optimization mechanism, which controls the Cl- concentration at the initial stage of the reaction and induces the formation of a precursor layered structure, thereby significantly improving the material purity and thus improving the long-cycle stability of the aluminum-based lithium adsorbent; by introducing a surfactant and a chloride salt compound, a through-going mesoporous channel is constructed, thereby improving the lithium ion diffusion rate; by combining the interface modifier with the Al 3+ The chelation effect of the aluminum-based lithium adsorbent exposes the highly active (003) crystal facets, thereby increasing the lithium adsorption capacity of the aluminum-based lithium adsorbent to 10-15 mg / g. The aluminum-based lithium adsorbent obtained using this method exhibits advantages such as high purity (≥95%), high adsorption capacity, high lithium raw material utilization, and long-term cycle stability. It provides an efficient and low-cost industrial solution for lithium extraction from salt lakes and recycling of used lithium batteries.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing an aluminum-based lithium adsorbent, the preparation method comprising the following steps:
[0009] A lithium aluminum mixed salt solution, an alkali solution-interface regulator composite solution and a chloride salt-surfactant mixed solution are mixed to carry out a co-precipitation reaction, and a precursor precipitate is obtained after solid-liquid separation.
[0010] The precursor precipitate is post-processed to obtain an aluminum-based lithium adsorbent.
[0011] The present invention provides a dual-track collaborative optimization mechanism of "impurity suppression-morphology control". By controlling the Cl- concentration in the early stage of the reaction, the formation of the precursor layered structure is directional induced, which significantly improves the purity of the material, making the purity of the aluminum-based lithium adsorbent ≥95%, thereby improving the long-term cycle stability of the aluminum-based lithium adsorbent; by introducing a surfactant and a chloride salt compound, the construction of a through-going mesoporous channel is achieved, which improves the lithium ion diffusion rate; by combining the interface regulator with Al 3+ The chelation effect of the aluminum-based lithium adsorbent exposes the highly active (003) crystal facets, increasing the lithium adsorption capacity of the aluminum-based lithium adsorbent to 10-15 mg / g. Furthermore, this method has an extremely high lithium raw material utilization rate of over 90%.
[0012] The method provided by the present invention has a simple preparation process, a short synthesis route, low energy consumption, does not require complicated equipment and processing technology, saves costs, and is suitable for large-scale production and application.
[0013] Based on the method provided by the present invention, the controllable synthesis of the layered structure of aluminum-based lithium adsorbent is realized. The obtained aluminum-based lithium adsorbent has the advantages of high purity, high adsorption capacity, high lithium raw material utilization rate and long-cycle stability. It is applied to fields such as lithium extraction from salt lakes or recycling of waste lithium batteries, can improve the extraction efficiency of lithium ions, reduce operating costs, alleviate the problem of lithium resource shortage, and has good application prospects.
[0014] Preferably, in the lithium aluminum mixed salt solution, the lithium salt includes any one or a combination of at least two of lithium hydroxide, lithium chloride, lithium nitrate or lithium sulfate. Typical but non-limiting combinations are lithium hydroxide and lithium sulfate, lithium hydroxide and lithium chloride, etc., preferably lithium chloride and / or lithium hydroxide, and more preferably lithium chloride.
[0015] Preferably, in the lithium aluminum mixed salt solution, the aluminum salt includes any one or a combination of at least two of aluminum hydroxide, aluminum chloride, aluminum nitrate or aluminum sulfate. Typical but non-limiting combinations are aluminum hydroxide and aluminum sulfate, aluminum hydroxide and aluminum chloride, etc., preferably aluminum chloride and / or aluminum hydroxide, and more preferably aluminum chloride.
[0016] Preferably, the lithium ion concentration in the lithium aluminum mixed salt solution is 0.2-1.0 mol / L, for example, 0.2 mol / L, 0.4 mol / L, 0.6 mol / L, 0.8 mol / L, or 1.0 mol / L. Due to space limitations and for the sake of brevity, the present invention does not exhaustively list the specific values included in the range.
[0017] Preferably, the concentration of aluminum ions in the lithium aluminum mixed salt solution is 0.5-2.8 mol / L, for example, 0.5 mol / L, 1.0 mol / L, 1.5 mol / L, 2.0 mol / L, 2.5 mol / L or 2.8 mol / L, preferably 1.0-2.5 mol / L, more preferably 1.9 mol / L. Due to space limitations and for the sake of simplicity, the present invention does not exhaustively list the specific values included in the range.
[0018] Preferably, in the lithium-aluminum mixed salt solution, the molar ratio of aluminum ions to lithium ions is (1.8-2.5):1, for example, 1.8:1, 1.9:1, 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, or 2.5:1, and preferably 2.05:1. Due to space limitations and for the sake of brevity, the present invention does not exhaustively list the specific values included in the range.
[0019] In the present invention, the appropriate molar ratio of aluminum ions to lithium ions is the key to preparing high-performance aluminum-based lithium adsorbents. If the molar ratio is too low, the lithium active sites generated by the obtained aluminum-based lithium adsorbent are low, which in turn leads to a low adsorbent capacity; if the molar ratio is too high, the intercalation efficiency of the chloride salt is low, which easily leads to waste of lithium raw materials.
[0020] Preferably, in the alkali solution-interface modifier composite solution, the alkali solution includes any one or a combination of at least two of sodium hydroxide, sodium carbonate, lithium hydroxide, potassium hydroxide or ammonia water. Typical but non-limiting combinations are sodium hydroxide and lithium hydroxide, sodium hydroxide and ammonia water, etc., preferably sodium hydroxide and / or ammonia water, more preferably sodium hydroxide.
[0021] Preferably, in the alkali solution-interface regulator composite solution, the interface regulator includes any one or a combination of at least two of ethylenediaminetetraacetic acid (EDTA), triethanolamine (TEA) or citric acid, preferably ethylenediaminetetraacetic acid and / or triethanolamine, and more preferably triethanolamine.
[0022] Preferably, the concentration of the alkali solution in the alkali solution-interface modifier composite solution is 1-10 mol / L, for example, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, or 10 mol / L, preferably 2-8 mol / L, and more preferably 4.2 mol / L. Due to space limitations and for the sake of simplicity, the present invention does not exhaustively list the specific values included in the above ranges.
[0023] In the present invention, the concentration of the alkali solution is a key variable in the coprecipitation reaction, determining the capacity and particle size distribution of the aluminum-based lithium adsorbent. Excessive alkali concentration leads to excessive ionic strength, resulting in excessive compression of the particle double layer and secondary particle agglomeration, leading to excessively large product particle size, reduced specific surface area, and insufficient exposure of active sites. Excessive alkali concentration leads to insufficient OH- supply, resulting in a decreased metal ion hydrolysis rate and a reduced yield per unit time.
[0024] Preferably, the concentration of the interface modifier in the alkali solution-interface modifier composite solution is 0.1-1.0 mol / L, for example, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L or 1.0 mol / L, preferably 0.15-0.6 mol / L, more preferably 0.5 mol / L. Due to space limitations and for the sake of simplicity, the present invention does not exhaustively list the specific values included in the range.
[0025] In the present invention, the concentration of the interface modifier is the key to the structural stability of the aluminum-based lithium adsorbent. The functional groups on the interface modifier will react with the Al 3+ The formation of a stable multidentate complex regulates crystal face growth and improves lithium adsorption capacity. If the concentration of the interface modulator is too low, the crystal face regulation effect is poor and the improvement in lithium ion adsorption capacity is not obvious. If the concentration of the interface modulator is too high, the alkaline environment induced by the interface modulator will lead to atomic rearrangement and lattice distortion within the material, resulting in a decrease in crystallinity and failure of crystal face regulation.
[0026] Preferably, in the chloride salt-surfactant mixture, the chloride salt includes any one or a combination of at least two of sodium chloride, potassium chloride, lithium chloride or ammonium chloride, preferably sodium chloride and / or potassium chloride, and more preferably sodium chloride.
[0027] Preferably, in the chloride salt-surfactant mixture, the surfactant is a nonionic surfactant.
[0028] Preferably, the nonionic surfactant includes any one or a combination of at least two of polyethylene glycol, sodium lauryl sulfate, polyvinyl pyrrolidone (PVP) or octadecyl trimethyl ammonium bromide (OTAB), preferably polyvinyl pyrrolidone and / or octadecyl trimethyl ammonium bromide, and further preferably polyvinyl pyrrolidone.
[0029] Preferably, the PVP comprises PVP K17 (molecular weight ≈ 9×10 3 )、PVP K25(molecular weight≈3.4×10 4 )、PVP K30(molecular weight≈5.4×10 4 ) or PVP K90 (molecular weight ≈ 11×10 5 ) or a combination of at least two thereof, preferably PVP K25.
[0030] Preferably, the concentration of the chloride salt in the chloride salt-surfactant mixture is 0.1-4 mol / L, for example, 0.1 mol / L, 0.5 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, or 4 mol / L, preferably 1.5-3 mol / L, and more preferably 2 mol / L. Due to space limitations and for the sake of brevity, the present invention does not exhaustively list the specific values included in the range.
[0031] In the present invention, the concentration of chloride salt in the coprecipitation reaction is the key to preparing high-purity aluminum-based lithium adsorbent. An appropriate concentration of chloride ions can promote the formation of a layered structure of the aluminum-based lithium adsorbent. If the concentration is too low, the purity of the prepared aluminum-based lithium adsorbent is poor, which is manifested as a decrease in adsorption capacity. If the concentration is too high, it means that the initial system of the coprecipitation reaction is oversaturated with chloride ions, causing the solution viscosity to increase, hindering the mass transfer efficiency, and also being unfavorable for improving the adsorption capacity.
[0032] Preferably, the concentration of the surfactant in the chloride salt-surfactant mixture is 0.05-0.15 g / L, for example, 0.05 g / L, 0.075 g / L, 0.1 g / L, 0.125 g / L, or 0.15 g / L, and preferably 0.1 g / L. Due to space limitations and for the sake of brevity, the present invention does not exhaustively enumerate the specific values included in the aforementioned ranges.
[0033] In the present invention, an appropriate concentration of surfactant in the coprecipitation reaction facilitates the dispersion of the primary nucleated particles and is key to improving the utilization rate of the lithium raw material. If the concentration is too low, the reaction system does not reach the micelle concentration, the surfactant has a limited effect, the surface energy of the aluminum-based lithium adsorbent particles is not effectively reduced, and the particles agglomerate significantly. If the concentration is too high, excessive molecular chains entangle, resulting in a significant increase in solution viscosity, hindering the mass transfer process, and potentially covering active sites, reducing the lithium adsorption capacity.
[0034] Preferably, the mixing method comprises:
[0035] The lithium aluminum mixed salt solution and the alkali solution-interface regulator composite solution are pumped into the reactor containing the chloride salt-surfactant mixed solution in parallel.
[0036] Preferably, the flow rate of the lithium aluminum mixed salt solution is 4-12 mL / min, for example, 4 mL / min, 6 mL / min, 8 mL / min, 10 mL / min, or 12 mL / min, and preferably 5 mL / min. Due to space limitations and for the sake of simplicity, the present invention does not exhaustively list the specific points included in the above ranges.
[0037] Preferably, the flow rate of the alkali solution-interface modifier composite solution is 2-8 mL / min, for example, 2 mL / min, 3 mL / min, 4 mL / min, 5 mL / min, 6 mL / min, 7 mL / min, or 8 mL / min, and preferably 7.5 mL / min. Due to space limitations and for the sake of brevity, the present invention does not exhaustively list the specific values included in the aforementioned ranges.
[0038] In the present invention, if the flow rate of the lithium-aluminum mixed salt solution or the flow rate of the alkali solution-interface regulator composite solution is too high, it is easy to cause the diffusion path of Li+ in the aluminum-based skeleton to be blocked by amorphous Al(OH)3, and the adsorption capacity of the aluminum-based lithium adsorbent is significantly attenuated; if the flow rate of the lithium-aluminum mixed salt solution or the flow rate of the alkali solution-interface regulator composite solution is too low, it is easy to cause the particle collision frequency to decrease, and the high-energy sites that are not passivated on the surface induce heterogeneous adsorption, forming hard agglomerates with a particle size of more than 1μm, which cover the lithium active sites.
[0039] Preferably, before the coprecipitation reaction, the preheating temperature of the chloride salt-surfactant mixture in the reactor is 60-70° C., for example, 60° C., 62° C., 64° C., 66° C., 68° C., or 70° C. The specific values between the above values are not exhaustively listed in the present invention due to space limitations and for the sake of simplicity.
[0040] Preferably, the reaction temperature of the coprecipitation reaction is 40-80° C., for example, 40° C., 45° C., 50° C., 55° C., 60° C., 65° C., 70° C., 75° C. or 80° C., preferably 60-70° C., more preferably 65° C. Specific values between the above values are not exhaustively listed in the present invention due to space limitations and for the sake of simplicity.
[0041] In the present invention, a suitable reaction temperature can, on the one hand, prevent high temperature from destroying the micelle stability of the surfactant, and on the other hand, promote the mass transfer process and improve the utilization rate of raw materials.
[0042] Preferably, the coprecipitation reaction is accompanied by stirring at a rate of 150-300 rpm, for example, 150 rpm, 175 rpm, 200 rpm, 225 rpm, 250 rpm, 275 rpm, or 300 rpm. Due to space limitations and for the sake of brevity, the present invention does not exhaustively list the specific values included in the range.
[0043] Preferably, the reaction endpoint of the coprecipitation reaction satisfies: the pH value of the reaction system is 6.0-8.5, for example, 6.0, 6.5, 7, 7.5, 8 or 8.5, preferably 6.9. Due to space limitations and for the sake of brevity, the present invention does not exhaustively list the specific values included in the range.
[0044] Preferably, the post-treatment comprises drying, cooling and grinding performed in sequence.
[0045] After the coprecipitation reaction, the present invention does not require aging treatment because the method adopted by the present invention uses chloride ion control, which is conducive to the formation of a layered structure. Therefore, after the reaction is completed, the suspension is directly filtered and washed to obtain a precursor precipitate.
[0046] Preferably, the drying temperature is 40-95°C, for example, it can be 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or 95°C, etc., and the specific point values between the above values are not exhaustively listed in the present invention due to space limitations and for the sake of simplicity.
[0047] It should be noted that the present invention does not limit the specific drying time, as long as the moisture content of the precursor precipitate does not exceed 5%.
[0048] In a second aspect, the present invention provides an aluminum-based lithium adsorbent, which is prepared using the preparation method described in the first aspect.
[0049] The chemical formula of the aluminum-based lithium adsorbent is LiCl·mAl(OH)3·nH2O, wherein m=1.5-2.1, for example, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, or 2.1, and n=1-9, for example, 1, 2, 3, 4, 5, 6, 7, 8, or 9. Due to space limitations and for the sake of brevity, the present invention does not exhaustively list the specific values within the aforementioned ranges.
[0050] Preferably, the aluminum-based lithium adsorbent has a median particle size of 0.1-10 μm, for example, 0.1 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, or 10 μm. Due to space limitations and for the sake of brevity, the present invention does not exhaustively list the specific values within the aforementioned ranges.
[0051] Preferably, the BET specific surface area of the aluminum-based lithium adsorbent is 130-150 m 2 / g, for example, it can be 130m 2 / g, 135m 2 / g, 140m 2 / g, 145m 2 / g or 150m 2 Due to space limitations and for the sake of brevity, the present invention will no longer exhaustively list the specific values included in the ranges above.
[0052] In the present invention, the aluminum-based lithium adsorbent has a higher BET specific surface area, which enables it to obtain better lithium adsorption capacity.
[0053] In a third aspect, the present invention provides an application of the aluminum-based lithium adsorbent as described in the second aspect in the field of lithium extraction from salt lakes or the field of waste lithium battery recycling.
[0054] The lithium extraction mechanism of the aluminum-based lithium adsorbent provided by the present invention is:
[0055] The synthesized aluminum-based lithium adsorbent was decomposed into a portion of Li + Deintercalation from the structure forms Al-O octahedral cavities. When the adsorbent comes into contact with salt lake brine, the Li + The selectivity of this process is mainly due to two mechanisms:
[0056] 1) Memory effect: the hole retains the Li + coordination memory, tending to rebind with the same ion;
[0057] 2) Steric effect: The size and charge distribution of the hole have an impact on other ions (such as Na + , K + ) forms spatial repulsion.
[0058] Therefore, the adsorption-desorption mechanism can be described as follows: the preformation of the vacancy and the Li + The specific recognition of lithium ions can achieve efficient and selective adsorption, and its adsorption and analysis mechanism can be expressed as follows:
[0059] The numerical range described in the present invention includes not only the point values listed above, but also any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0060] Compared with the prior art, the present invention has the following beneficial effects:
[0061] (1) The present invention provides a dual-track collaborative optimization mechanism of "impurity suppression-morphology control". By controlling the Cl- concentration in the initial stage of the reaction, the formation of the precursor layered structure is directional induced, which significantly improves the purity of the material, making the purity of the aluminum-based lithium adsorbent ≥95%, thereby improving the long-term cycle stability of the aluminum-based lithium adsorbent; by introducing a surfactant and a chloride salt composite, the construction of a through-going mesoporous channel is achieved, which improves the lithium ion diffusion rate; by the interface regulator and Al 3+ The chelation effect of the aluminum-based lithium adsorbent exposes the highly active (003) crystal facets, increasing the lithium adsorption capacity of the aluminum-based lithium adsorbent to 10-15 mg / g. Furthermore, this method has an extremely high lithium raw material utilization rate of over 90%.
[0062] (2) The method provided by the present invention has a simple preparation process, a short synthesis route, low energy consumption, and does not require complicated equipment and processing technology, thus saving costs and being suitable for large-scale production and application.
[0063] (3) Based on the method provided by the present invention, the controllable synthesis of the layered structure of aluminum-based lithium adsorbent is achieved. The obtained aluminum-based lithium adsorbent has the advantages of high purity, high adsorption capacity, high lithium raw material utilization rate and long cycle stability. It is applied to the fields of salt lake lithium extraction or waste lithium battery recycling, etc., which can improve the extraction efficiency of lithium ions, reduce operating costs, alleviate the problem of lithium resource shortage, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] Figure 1 This is a SEM image of the aluminum-based lithium adsorbent prepared in Example 1 of the present invention.
[0065] Figure 2 This is a SEM image of the aluminum-based lithium adsorbent prepared in Comparative Example 1 of the present invention.
[0066] Figure 3 1 and 2 are XRD comparison diagrams of the aluminum-based lithium adsorbents prepared in Example 1 and Comparative Example 1 of the present invention, respectively. DETAILED DESCRIPTION
[0067] The technical solution of the present invention is further described below by way of specific embodiments. It should be understood by those skilled in the art that the embodiments are merely to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0068] Example 1
[0069] This embodiment provides a method for preparing an aluminum-based lithium adsorbent, the preparation method comprising the following steps:
[0070] (1) Weigh 458.7 g of AlCl3·6H2O (analytical grade, purity above 99.7%) and 55.98 g of LiCl·H2O (analytical grade) into a beaker, add a certain volume of deionized water, stir and dissolve, and then adjust the volume to 1000 mL to obtain a lithium-aluminum salt mixture, in which the concentration of aluminum ions is 1.9 mol / L, the concentration of lithium ions is 0.927 mol / L, and the molar ratio of aluminum ions to lithium ions is 2.05:1.
[0071] 504.0 g of NaOH (analytical grade) and 223.8 g of TEA (analytical grade) were weighed and poured into a beaker. A certain volume of deionized water was added, stirred and dissolved, and the volume was adjusted to 3000 mL to obtain an alkali solution-interface regulator composite solution, in which the concentration of NaOH was 4.2 mol / L and the concentration of TEA was 0.5 mol / L.
[0072] Weigh 0.1 g of PVP (industrial grade, model PVP K25) and 116.8 g of NaCl (analytical grade) into a beaker, add a certain volume of deionized water, stir to dissolve, and then dilute to 1000 mL to obtain a chloride-surfactant mixture, in which the concentration of PVP is 0.1 g / L and the concentration of NaCl is 2 mol / L.
[0073] (2) In a double-layer glass reactor, 500 mL of the chloride salt-surfactant mixture was added as a base liquid and preheated to 65° C., and then the lithium aluminum salt mixture and the alkali solution-interface regulator composite solution were pumped into the double-layer glass reactor in a parallel flow manner using a peristaltic pump. A coprecipitation reaction was carried out at 120 rpm and 65° C. When the pH value of the reaction system reached 6.9, the reaction was terminated, and then the precursor precipitate was filtered and washed to obtain a precursor precipitate.
[0074] The flow rate of the lithium aluminum salt mixed solution is 5 mL / min, and the flow rate of the alkali solution-interface regulator composite solution is 7.5 mL / min.
[0075] (3) The precursor precipitate is placed in an oven at 50° C. and dried to reduce the moisture content to 5%, and then cooled and ground to obtain an aluminum-based lithium adsorbent having the chemical formula LiCl·mAl(OH)3·nH2O, wherein m=2 and n=5.
[0076] Figure 1 The SEM image of the aluminum-based lithium adsorbent prepared in this embodiment is shown. As can be seen from the figure, its particle size is small, the particles are not agglomerated and bonded, the dispersion is good, and the morphology shows an irregular shape. The edges of these materials provide abundant defects and lithium active sites.
[0077] Example 2
[0078] The difference between this embodiment and embodiment 1 is that the concentration of aluminum ions in the lithium aluminum salt mixture in step (1) is 2.32 mol / L.
[0079] The rest of the preparation methods and parameters remained the same as in Example 1.
[0080] Example 3
[0081] The difference between this embodiment and embodiment 1 is that the concentration of aluminum ions in the lithium aluminum salt mixture in step (1) is 1.71 mol / L.
[0082] The rest of the preparation methods and parameters remained the same as in Example 1.
[0083] Example 4
[0084] The difference between this embodiment and embodiment 1 is that the concentration of NaOH in the alkali solution-interface regulator composite solution in step (1) is 2 mol / L.
[0085] The rest of the preparation methods and parameters remained the same as in Example 1.
[0086] Example 5
[0087] The difference between this embodiment and embodiment 1 is that the concentration of NaOH in the alkali solution-interface regulator composite solution in step (1) is 8 mol / L.
[0088] The rest of the preparation methods and parameters remained the same as in Example 1.
[0089] Example 6
[0090] The difference between this embodiment and embodiment 1 is that the concentration of TEA in the alkali solution-interface regulator composite solution in step (1) is 0.12 mol / L.
[0091] The rest of the preparation methods and parameters remained the same as in Example 1.
[0092] Example 7
[0093] The difference between this embodiment and embodiment 1 is that the concentration of TEA in the alkali solution-interface regulator composite solution in step (1) is 0.8 mol / L.
[0094] The rest of the preparation methods and parameters remained the same as in Example 1.
[0095] Example 8
[0096] The difference between this embodiment and embodiment 1 is that the concentration of PVP in the chloride salt-surfactant mixture in step (1) is 0.05 g / L.
[0097] The rest of the preparation methods and parameters remained the same as in Example 1.
[0098] Example 9
[0099] The difference between this embodiment and embodiment 1 is that the concentration of PVP in the chloride salt-surfactant mixture in step (1) is 0.15 g / L.
[0100] The rest of the preparation methods and parameters remained the same as in Example 1.
[0101] Example 10
[0102] The difference between this embodiment and embodiment 1 is that the concentration of NaCl in the chloride salt-surfactant mixture in step (1) is 1.5 mol / L.
[0103] The rest of the preparation methods and parameters remained the same as in Example 1.
[0104] Example 11
[0105] The difference between this embodiment and embodiment 1 is that the concentration of NaCl in the chloride salt-surfactant mixture in step (1) is 3 mol / L.
[0106] The rest of the preparation methods and parameters remained the same as in Example 1.
[0107] Example 12
[0108] The difference between this embodiment and embodiment 1 is that the flow rate of the lithium aluminum salt mixture in step (2) is 4 mL / min.
[0109] The rest of the preparation methods and parameters remained the same as in Example 1.
[0110] Example 13
[0111] The difference between this embodiment and embodiment 1 is that the flow rate of the lithium aluminum salt mixture in step (2) is 12 mL / min.
[0112] The rest of the preparation methods and parameters remained the same as in Example 1.
[0113] Example 14
[0114] The difference between this embodiment and embodiment 1 is that the flow rate of the alkali solution-interface regulator composite solution in step (2) is 8 mL / min.
[0115] The rest of the preparation methods and parameters remained the same as in Example 1.
[0116] Example 15
[0117] The difference between this embodiment and embodiment 1 is that the flow rate of the alkali solution-interface regulator composite solution in step (2) is 2 mL / min.
[0118] The rest of the preparation methods and parameters remained the same as in Example 1.
[0119] Example 16
[0120] The difference between this embodiment and embodiment 1 is that the concentration of NaOH in the alkali solution-interface regulator composite solution in step (1) is 11 mol / L.
[0121] The rest of the preparation methods and parameters remained the same as in Example 1.
[0122] Example 17
[0123] The difference between this embodiment and embodiment 1 is that when the reaction is terminated in step (2), the pH value of the reaction system is 9.
[0124] The rest of the preparation methods and parameters remained the same as in Example 1.
[0125] Example 18
[0126] The difference between this embodiment and embodiment 1 is that in the lithium aluminum salt mixture in step (1), the concentration of aluminum ions is 3 mol / L, so that the molar ratio of aluminum ions to lithium ions is 3.3:1.
[0127] The rest of the preparation methods and parameters remained the same as in Example 1.
[0128] Example 19
[0129] The difference between this embodiment and embodiment 1 is that the flow rate of the lithium aluminum salt mixture in step (2) is 15 mL / min.
[0130] The rest of the preparation methods and parameters remained the same as in Example 1.
[0131] Example 20
[0132] The difference between this embodiment and embodiment 1 is that the flow rate of the alkali solution-interface regulator composite solution in step (2) is 10 mL / min.
[0133] The rest of the preparation methods and parameters remained the same as in Example 1.
[0134] Comparative Example 1
[0135] The difference between this comparative example and Example 1 is that the chloride salt-surfactant mixture is not configured as the base liquid in step (1), and the base liquid in the double-layer glass reactor in step (2) is 500 mL of pure water.
[0136] The rest of the preparation methods and parameters remained the same as in Example 1.
[0137] Figure 2 The SEM image of the aluminum-based lithium adsorbent prepared in this comparative example is shown. As can be seen from the image, the particles agglomerate, resulting in large particle size and insufficient exposure of active sites.
[0138] Figure 3 The XRD comparison diagrams of the aluminum-based lithium adsorbents prepared in Example 1 and Comparative Example 1 are shown. It can be seen from the figure that the aluminum-based lithium adsorbent prepared in Example 1 is of high purity and no aluminum hydroxide is generated, while Comparative Example 1 produces more aluminum hydroxide, resulting in poor adsorbent purity, which in turn affects the lithium extraction performance.
[0139] Comparative Example 2
[0140] The difference between this comparative example and Example 1 is that PVP is not added in step (1), so that the chloride salt-surfactant mixture in step (1) is converted into a pure chloride salt solution.
[0141] The rest of the preparation methods and parameters remained the same as in Example 1.
[0142] Comparative Example 3
[0143] The difference between this comparative example and Example 1 is that NaCl is not added in step (1), so that the chloride salt-surfactant mixture in step (1) is converted into a pure surfactant solution.
[0144] The rest of the preparation methods and parameters remained the same as in Example 1.
[0145] Comparative Example 4
[0146] The difference between this comparative example and Example 1 is that TEA is not added in step (1), so that the alkali solution-interface modifier composite solution in step (1) is converted into pure alkali solution.
[0147] The rest of the preparation methods and parameters remained the same as in Example 1.
[0148] Performance Testing
[0149] 1. The aluminum-based lithium adsorbents prepared in the above examples and comparative examples were tested for median particle size, BET surface area, and total organic carbon analysis (TOC analysis). The median particle size was measured using dynamic light scattering (DLS), and TOC analysis was performed by converting organic matter into CO2 for quantitative analysis via combustion.
[0150] The test results are shown in Table 1.
[0151] Table 1
[0152]
[0153]
[0154] analyze:
[0155] The TOC data analysis in Table 1 shows that after the interface modifier and surfactant introduced during the preparation process were activated with pure water, neither remained significantly in the powder, and did not cause organic contamination in the subsequent lithium extraction solution. The median particle size and specific surface area data indicate that the aluminum-based lithium adsorbent synthesized using the method provided by the present invention has a small median particle size and a large specific surface area, indicating that the present invention effectively controls particle dispersion and prevents hard agglomeration, which is beneficial for increasing the rate of lithium ion diffusion and improving lithium ion adsorption.
[0156] 2. The aluminum-based lithium adsorbents prepared in the above embodiments and comparative examples and pure water were placed on a shaker at a solid-liquid ratio of 1 g:100 mL, and then shaken at 180 rpm for 24 h for initial activation. The mixture was then filtered, and after draining the water, it was added to the salt lake brine with the composition shown in Table 2 at the same solid-liquid ratio (1 g:100 mL brine) for lithium ion adsorption. The adsorption shaker parameters were the same as the activation conditions, and the adsorption temperature was 40°C. After 24 h of adsorption, the mixture was filtered, and the filtrate was sampled and sent for inspection. The adsorption capacity of the aluminum-based lithium adsorbent was tested by ICP. The powder after lithium ion adsorption was analyzed at a solid-liquid ratio of 1 g powder:100 mL pure water, and the analysis shaker parameters were the same as the activation conditions. Adsorption-analysis was one cycle, and 20 cycles were performed to calculate the adsorption capacity decay rate.
[0157] Adsorption capacity (mg / g) = ((liquid lithium concentration after adsorption - brine lithium concentration) × brine volume) / mass of aluminum-based lithium adsorbent; wherein, the unit of liquid lithium concentration after adsorption is g / L, the unit of brine lithium concentration is g / L, the unit of brine volume is m, and the unit of aluminum-based lithium adsorbent mass is g.
[0158] Adsorption capacity decay rate (%) = ((adsorption capacity in the first cycle - adsorption capacity after 5 cycles) / adsorption capacity in the first cycle) × 100.
[0159] The K value method (internal standard method) is used to analyze the aluminum hydroxide content of the aluminum-based lithium adsorbent. The specific steps are as follows: 10 wt% of the internal standard substance (α-Al2O3) is added to the aluminum-based lithium adsorbent, and the aluminum hydroxide content is estimated by measuring the diffraction peak intensity ratio of the target phase (aluminum hydroxide) and the internal standard phase using the following formula:
[0160]
[0161] Lithium utilization rate in lithium-aluminum salt mixture: The lithium content of the lithium-aluminum salt mixture before the coprecipitation reaction and the lithium content in the filtrate after the reaction were measured by ICP, and the lithium utilization rate was calculated by mass ratio:
[0162] Lithium utilization rate (%) = lithium content in the filtrate after the reaction / lithium content of the lithium aluminum salt mixture before the coprecipitation reaction.
[0163] The test results are shown in Table 3.
[0164] Table 2
[0165] Components Li Na <![CDATA[SO4 2- ]]> K <![CDATA[Cl - ]]> pH content 0.32 75.0 10.0 20.0 135.0 7.0
[0166] Table 3
[0167]
[0168]
[0169] analyze:
[0170] As can be seen from Table 3, in the aluminum-based lithium adsorbent obtained by the present invention through the dual-track synergistic optimization mechanism of "impurity suppression-morphology regulation", particle agglomeration is reduced, and the lithium utilization rate is improved. Higher lithium utilization means efficient intercalation of lithium ions and lower production costs. At the same time, it provides abundant lithium effective sites for the effective adsorption of lithium in salt lake brine, thereby greatly increasing the adsorption capacity of the aluminum-based lithium adsorbent for lithium. After 20 adsorption-desorption cycles, the optimal adsorption capacity attenuation rate can be as low as 0.5%, showing good structural stability and cycle performance.
[0171] By comparing Example 1, Examples 8-11 with Comparative Examples 1-3, it can be seen that the synergistic effect of the concentration of chloride ions and PVP in the base solution is a key control factor in the preparation of high-purity aluminum-based lithium adsorbents. Specifically: (1) The concentration of sodium chloride is preferably controlled within the range of 1.5-3 mol / L. As a counterion to balance the charge, it can effectively stabilize the layered structure during the lithium ion insertion process, avoid lattice distortion, and help improve the structural stability of the adsorbent during long-term operation. However, in Comparative Examples 1 and 3, insufficient chloride ions lead to excessive aluminum hydroxide generation, and the adsorption capacity attenuation rate reaches 6%; (2) When the amount of PVP added is 0.05-0.15 g / L, the steric hindrance effect inhibits particle agglomeration, thereby reducing the ion intercalation resistance. In summary, the synergistic optimization of the concentrations of chloride ions and PVP in the base solution can increase the lithium adsorption capacity of the aluminum-based lithium adsorbent to 2.7 times that of Comparative Example 1.
[0172] From the comparison of Example 1, Examples 4-7, Example 16 and Comparative Example 4, it can be seen that the concentration of the interface modifier TEA and the concentration of the alkali solution are the key to preparing high-performance aluminum-based lithium adsorbents. 3+ A stable multidentate complex is formed to regulate crystal face growth. If the concentration is low, the crystal face regulation effect is poor, and the lithium ion sieve adsorption capacity improvement effect is not obvious. If the concentration is high, the alkaline environment induced by TEA may cause atomic rearrangement and lattice distortion inside the material, and the crystallinity decreases, which is not conducive to the adsorption of lithium ions. If the concentration of the alkali solution is too high, the high ionic strength compresses the double layer, which easily causes secondary agglomeration of particles, resulting in excessively large product particle size, decreased specific surface area, and insufficient exposure of active sites. Therefore, the synergistic optimization of the concentration of the interface regulator TEA and the concentration of the alkali solution can make the lithium adsorption capacity of the material reach 15 mg / g, showing an excellent synergistic effect.
[0173] Comparison of Examples 1, 12-15, and 17 with Examples 19-20 demonstrates that the flow rates of the alkali solution-interface modifier composite solution and the aluminum-lithium mixed salt solution, as well as the endpoint pH, are key process parameters of the present invention. These flow rates synergistically regulate the microscopic pH environment at the reaction interface. When the flow rate deviates from the optimized range defined by the present invention, local pH fluctuations exceed the stable operating window of the aluminum-lithium adsorbent, resulting in a decrease in its lithium ion adsorption capacity by more than 60%. This phenomenon demonstrates the decisive role of the flow rate parameter in material performance.
[0174] Comparison of Example 1 with Example 18 demonstrates that precise control of the aluminum ion to lithium ion molar ratio is a key parameter for achieving efficient lithium raw material utilization and also affects adsorbent performance. Excessively high aluminum ion to lithium ion molar ratios lead to excessive aluminum hydroxide production, which adversely affects adsorbent performance and cycle stability.
[0175] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing an aluminum-based lithium adsorbent, characterized in that: The preparation method comprises the following steps: A lithium aluminum mixed salt solution, an alkali solution-interface regulator composite solution and a chloride salt-surfactant mixed solution are mixed to carry out a coprecipitation reaction, and a precursor precipitate is obtained after solid-liquid separation; The precursor precipitate is post-processed to obtain an aluminum-based lithium adsorbent.
2. The preparation method according to claim 1, characterized in that In the lithium aluminum mixed salt solution, the lithium salt includes any one or a combination of at least two of lithium hydroxide, lithium chloride, lithium nitrate or lithium sulfate, preferably lithium chloride and / or lithium hydroxide, more preferably lithium chloride; Preferably, in the lithium aluminum mixed salt solution, the aluminum salt includes any one or a combination of at least two of aluminum hydroxide, aluminum chloride, aluminum nitrate or aluminum sulfate, preferably aluminum chloride and / or aluminum hydroxide, more preferably aluminum chloride; Preferably, the concentration of lithium ions in the lithium-aluminum mixed salt solution is 0.2-1.0 mol / L; Preferably, the concentration of aluminum ions in the lithium aluminum mixed salt solution is 0.5-2.8 mol / L, preferably 1.0-2.5 mol / L; Preferably, in the lithium-aluminum mixed salt solution, the molar ratio of aluminum ions to lithium ions is (1.8-2.5):
1.
3. The preparation method according to claim 1 or 2, characterized in that In the alkali solution-interface regulator composite solution, the alkali solution includes any one or a combination of at least two of sodium hydroxide, sodium carbonate, lithium hydroxide, potassium hydroxide or ammonia water, preferably sodium hydroxide and / or ammonia water, more preferably sodium hydroxide; Preferably, in the alkali solution-interface regulator composite solution, the interface regulator comprises any one of ethylenediaminetetraacetic acid, triethanolamine or citric acid, or a combination of at least two thereof, preferably ethylenediaminetetraacetic acid and / or triethanolamine, and more preferably triethanolamine; Preferably, in the alkali solution-interface regulator composite solution, the concentration of the alkali solution is 1-10 mol / L, preferably 2-8 mol / L; Preferably, in the alkali solution-interface regulator composite solution, the concentration of the interface regulator is 0.1-1.0 mol / L, preferably 0.15-0.6 mol / L.
4. The preparation method according to any one of claims 1 to 3, characterized in that In the chloride salt-surfactant mixture, the chloride salt includes any one or a combination of at least two of sodium chloride, potassium chloride, lithium chloride or ammonium chloride, preferably sodium chloride and / or potassium chloride, more preferably sodium chloride; Preferably, in the chloride salt-surfactant mixture, the surfactant is a nonionic surfactant; Preferably, the nonionic surfactant comprises any one or a combination of at least two of polyethylene glycol, sodium lauryl sulfate, polyvinyl pyrrolidone or octadecyl trimethyl ammonium bromide, preferably polyvinyl pyrrolidone and / or octadecyl trimethyl ammonium bromide, further preferably polyvinyl pyrrolidone; Preferably, the concentration of the chloride salt in the chloride salt-surfactant mixture is 0.1-4 mol / L, preferably 1.5-3 mol / L; Preferably, the concentration of the surfactant in the chloride salt-surfactant mixture is 0.05-0.15 g / L.
5. The preparation method according to any one of claims 1 to 4, characterized in that The mixing method includes: The lithium aluminum mixed salt solution and the alkali solution-interface regulator composite solution are pumped into the reactor containing the chloride salt-surfactant mixed solution in parallel; Preferably, the flow rate of the lithium aluminum mixed salt solution is 4-12 mL / min; Preferably, the flow rate of the alkali solution-interface regulator composite solution is 2-8 mL / min; Preferably, before the coprecipitation reaction, the preheating temperature of the chloride salt-surfactant mixture in the reactor is 60-70°C.
6. The preparation method according to any one of claims 1 to 5, characterized in that The reaction temperature of the coprecipitation reaction is 40-80°C, preferably 60-70°C; Preferably, the coprecipitation reaction is accompanied by stirring at a rate of 150-300 rpm; Preferably, the reaction endpoint of the coprecipitation reaction satisfies: the pH value of the reaction system is 6.0-8.
5.
7. The preparation method according to any one of claims 1 to 6, characterized in that The post-treatment includes drying, cooling and grinding performed in sequence; Preferably, the drying temperature is 40-95°C.
8. An aluminum-based lithium adsorbent, characterized in that The aluminum-based lithium adsorbent is prepared by the preparation method according to any one of claims 1 to 7; The chemical formula of the aluminum-based lithium adsorbent is LiCl·mAl(OH)3·nH2O, wherein m=1.5-2.1, and n=1-9.
9. The aluminum-based lithium adsorbent according to claim 8, characterized in that The median particle size of the aluminum-based lithium adsorbent is 0.1-10 μm; Preferably, the BET specific surface area of the aluminum-based lithium adsorbent is 130-150 m 2 / g.
10. Use of the aluminum-based lithium adsorbent according to claim 8 or 9 in the field of lithium extraction from salt lakes or the field of waste lithium battery recycling.
Citation Information
Cited By
Process for extracting lithium from lithium battery waste
CN121450925A
A method for preparing a layered double hydroxide lithium adsorbent
CN122441397A